All People Are [Not] Good - Trigger, Bruce G. (Anthropologica, 2022)
Richard Lee’s analysis of the role played by gossip and ridicule in maintaining political and economic equality in small-scale societies is reviewed from an evolutionary perspective. Comparative research on early civilizations suggests that, whenever the scale of society increases, these mechanisms eventually fail to be effective and force is used to protect political and economic privileges. While high-level decision making is required to manage complex political systems, this does not explain why managerial elites invariably appropriate disproportionate surpluses for their own use. Such behaviour questions the view that human beings are inherently altruistic, although sometimes corrupted by reactionary or unjust societies. While social engineering was able to curb inegalitarian behaviour in small-scale societies, industrial societies have yet to discover how to produce an analogous result.